1982
DOI: 10.5465/amr.1982.4285243
|View full text |Cite
|
Sign up to set email alerts
|

The Realistic Job Preview as a Persuasive Communication.

Abstract: BEFORE COMPLETING FORM I. REPORT NUMBER 2GVTACCESSION NO. 3. RECIPIENT'S CATALOG NUMBER 4. TITLE 'Id SubtIlo S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0
2

Year Published

1987
1987
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 16 publications
3
83
0
2
Order By: Relevance
“…Research on realistic job previews (RJPs) is rather thorough, beginning in 1956 with research by Weitz. Wanous (Wanous , , Popovich & Wanous , Premack & Wanous ) has done germane work with RJPs that has shown that their use lowers turnover as a post‐hire. The lower turnover is due to applicant self‐selection resulting from a realistic job preview.…”
Section: Model Implementation/resultsmentioning
confidence: 99%
“…Research on realistic job previews (RJPs) is rather thorough, beginning in 1956 with research by Weitz. Wanous (Wanous , , Popovich & Wanous , Premack & Wanous ) has done germane work with RJPs that has shown that their use lowers turnover as a post‐hire. The lower turnover is due to applicant self‐selection resulting from a realistic job preview.…”
Section: Model Implementation/resultsmentioning
confidence: 99%
“…Stress or perceived urgency inherent in the job interview situation combined with applicants' prior expectations or saliency of job-context characteristics are probably among the sources of their biased picture of what the job entails. Popovich and Wanous (1982) argued that the realistic job preview operates as a persuasive message influencing the recruit's attitudes toward the job. Thus, research efforts should address information processing.…”
Section: Discussionmentioning
confidence: 99%
“…Las expectativas a lo largo de la historia en la organización van siendo confrontadas con aquellas que incorporó desde que comenzó a formar parte de ella. Algunos estudios inclusive han profundizado sobre la importancia de la gestión de las expectativas como elemento clave para la retención de personas, desarrollando programas especí-ficos para ello (Papovich & Wanous, 1982;Wanous & Reichers, 2000).…”
Section: Egreso Voluntariounclassified